Paraplegia after sclerotherapy of varicose leg veins - Frings, N.; Brenner, E.; Prinz, N.; Glowacki, P.; Moersdorf, M.; Maschke, M. (Phlebologie, 2017)
We would like to present the case of paraplegia due to venous spinal ischaemia, which occurred after sclerotherapy of leg veins and subsequent to previous venous surgery. After exclusion of other pathogenetic causes such as surgery, tumescent local anaesthesia or neurological, infections, cardiological and haemosteaseological causes, this complication must be regarded as a consequence of sclerotherapy. Sources in literature describe shunts (shortened connections) between the leg veins and the venous spinal system, thus enabling minutest particles from sclerotherapy to enter the veins and possibly have a cytotoxic or microembolic effect with spinal ischaemia.Wir möchten den Fall einer Paraplegie aufgrund einer venösen spinalen Ischämie vorstellen, welche nach Sklerosierung von Beinvarizen bei vorausgegangener Varizenoperation aufgetreten ist. Nach Ausschluss von anderen pathogenetischen Ursachen wie Operation, Tumeszenzlokalanästhesie oder auch neurologische, infektiöse, kardiologisch- und hämostaseologische Ursachen muss diese Komplikation als Folge der Sklerosierung angesehen werden. In der Literatur werden Kurzschlussverbindungen zwischen dem Beinvenen- und dem venösen spinalen System beschrieben, so dass kleinste Verödungspartikel in die spinalen Venen gelangen können und hier eine zytotoxische oder mikroembolische Wirkung mit spinaler Ischämie bewirken können.
Keywords: Paraplegia; venous spinal ischaemia; venous sclerotherapy; venous surgery; tumescent local anaesthesia